Business process reengineering in a design and development environment - Chiang, Kum Chuen. (2008)
The purpose of this thesis is to describe the Business Process Reengineering effort for a vehicular design and development environment in a local company. It was recognised that there is a need to reengineer in view of the number of projects to be undertaken under a tighter delivery schedule. The synergy between Business Process Reengineering (BPR) and Product Data Management (PDM) is also discussed.